PERAN ISTRI DALAM MEMBANGUN EKONOMI KELUARGA MENURUT PERSPEKTIF HUKUM ISLAM DI KECAMATAN PANYABUNGAN KOTA - Dede Hafirman Said (Universitas Islam Negeri Sumatera Utara, 2020)
Pros and cons occur in society regarding the role of the wife and also as a career woman as well as the urgency of the wife to the impact of working women. People have started to open themselves up by allowing their wives to work as long as they do not violate their nature as a housewife with the aim of supporting the family's economy, although some are worried about the imbalance of these two roles in the family. This paper analyzes the efforts made by the wife who also works in the Panyabungan Kota District in building the family economy. This study used semi-structured in-depth interviews with 5 respondents. The results showed that the working wife has tips on managing income in order to build the family economy. Islam does not prohibit a wife from having a career, but a wife does work that does not contradict her feminine nature and does not confine her rights at work and can maintain her honor and avoid harassment and behavior in accordance with Islamic law. A working wife must be able to solve problems of family and work conflicts that often conflict with each other.